ELECTROSPUN PAN-MELAMINE COMPOSITE NANOFIBERS FOR THE ADSORPTION OF THE COMPOUND OF DI-(2-ETHYLHEXYL)PHTHALATE (DEHP). - Binuang Sujana, Nely
Di-(2-ethylhexyl)phthalate (DEHP) is one of the most abundant phthalic acid esters (PAEs) and is used in plastic products as a plasticizer. DEHP is not chemically bound to plastic, but only physically dissolved so that its use allows pollution to the aquatic environment. DEHP is toxic to the human endocrine and reproductive systems. Therefore, a technology for the removal of DEHP compounds is needed. Adsorption is the most widely used technique for the removal of DEHP compounds due to the simplicity of the method and cost effectiveness. Polymeric adsorbents such as PAN (Polyacrylonitrile) in the nano size range have a large surface area and can increase the adsorption capacity. Electrospinning is one of the simplest methods for producing nanoscale fibers. Modified polymer nanofibers can produce higher porosity and surface area with high specifications. Modification of amino groups such as melamine on the surface of nanomaterials is widely used to produce nitrogen containing functional groups (-C-N, -C=N, -NH, -NH2) to increase adsorption efficiency. The manufacture of functional materials begins with synthesizing PAN nanofibers and PAN-Melamine nanofibers through electrospinning with optimization conditions including variations in PAN solution concentration, flow rate, application of electric voltage, and the distance from the tip of the needle to the collector. The adsorbent was characterized by SEM and FTIR spectrometry. Evaluation of the adsorption performance of DEHP compounds by PAN and PAN-Melamine nanofibers was studied using the batch method by optimizing the effect of melamine concentration, contact time, and adsorption kinetics studies. The results showed that PAN and PAN-Melamine nanofibers had been successfully synthesized by electrospinning at optimum conditions of 14% PAN solution concentration, flow rate 0,5 ?L min-1, electric voltage 10,5 – 11,3 kV, and needle tip distance. to collector 15 cm. The addition of melamine changed the physical structure of the surface of the nanofibers with the average fiber diameter ranging from 350 – 400 nm when the concentration of melamine in the PAN solution increased. The FTIR spectrum of the PAN-Melamine nanofiber composite showed new distinctive peaks at wave numbers 812, 1025, 1659, 3472, 3418, 3324, and 3129 cm-1 which indicated the typical spectrum of melamine. The results of optimization of the adsorption capacity of DEHP compounds by PAN and PAN-Melamine nanofibers with various concentrations, obtained the optimum capacity at 0,10 g/mL variation of PAN-Melamine nanofibers, 120 minutes contact time with a pseudo first order kinetics model. The mechanism of separation of DEHP compounds from solution is controlled by intra- particle diffusion using Boyd's kinetic model.